The Pandek Work System as Capital in Realizing the Sustainability of Ornamental Grass Farming Communities - Sari, Ajeng Yuri Eka Sasmita; Rozuli, Ahmad Imron; Nurhadi, Iwan (LPPM Universitas PGRI Sumatera Barat, 2025)
This study examines the pandek traditional work system in ornamental grass farming in Sukolilo Village, Wajak District, Malang Regency, as a form of social capital that supports the sustainability of farmer communities. Pandek is a traditional work pattern without formal contracts based on trust, norms of reciprocity, and kinship networks. The research uses a qualitative approach with an explanatory case study method, and is analyzed through Putnam's social capital theory, specifically the concepts of bonding and bridging capital. The results show that the pandek system helps farmers save up to 20% of production costs through efficiency based on social solidarity. Bonding capital is evident in the relationship between large farmers who share information and resources, while the relationship between farmers and pandek laborers forms a patron-client pattern as a form of bridging capital. This system supports sustainability in three key aspects: economic (efficiency and job stability), social (cohesion and equitable resource distribution), and ecological (chemical-free agricultural practices). However, this system harbors a paradox: sustainability is achieved through unequal labor relations and low labor wages. Therefore, policy innovation based on strengthening social capital is needed to create more equitable sustainability at the local level.